Makna â€œMengambilâ€ Bahasa Bali: Pendekatan Metabahasa Semantik Alami (MSA) - Ni Nyoman Widani (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2016)
This research describes the meaning of the verb 'mengambil' in Balinese language based on the theory of Natural Semantics Metalanguage (NSM) by using one of NSM theory is noncomposition polysemy. This research is to obtain a comprehensive picture of the realization of the lexical verb â€œmengambilâ€ in Balinese languange, The data of this research was obtained from Balinese people serounding who communicate in Balinese languange and the author's own intuition because the author is a native speaker of the Balinese language used.Â The method used in this research is descriptive-qualitative method, the data will be analyzed by using the theory of NSM by following the steps as follows: the classification of the data, analyze the semantic structure of the verb 'mengambil', and describes the components obtained resulting configuration meaning the user to obtain the feature distinctive. Furthermore, the technique of paraphrasing would look if there lexicon 'mengambil' that has a paraphrase of the same or different depending on the meaning of default is used. Based on the analysis conducted found that the verb â€œmengambilâ€' in Balinese language can be expressed in some lexicons, they are: â€œnyemak/ngambil, nyuang, nuduk, nimba, ngarebut, nyopÃ¨t, ngarampok, nyambrÃ¨t, ngamaling dan ngutilâ€Â Keywords: Semantic role, verb â€œmengambilâ€ Balinese language, natural semantic metalanguage